Targetable gene fusions identified in radioactive iodine refractory advanced thyroid carcinoma. Issue 4 (April 2019) - van der Tuin, K; Ventayol Garcia, M; Corver, W E; Khalifa, M N; Ruano Neto, D; Corssmit, E P M; Hes, F J; Links, T P; Smit, J W A; Plantinga, T S; Kapiteijn, E; van Wezel, T; et al.
Abstract : Objective: Gene alterations leading to activation of the MAPK pathway are of interest for targeted therapy in patients with advanced radioactive iodine refractory (RAI-R) thyroid carcinoma. Due to technical reasons gene fusion analysis in RNA isolated from formalin-fixed tumor tissues has till now been limited. The objective of the present study was to identify targetable gene rearrangements in RNA isolated from formalin-fixed RAI-R thyroid carcinomas. Design: Retrospective study in 132 patients with RAI-R thyroid carcinoma (59 papillary-, 24 follicular-, 35 Hürthle cell- and 14 anaplastic thyroid carcinoma). Methods: Total nucleic acid (undivided DNA and RNA) was isolated from formalin-fixed tissue. Extensive gene fusion analysis was performed in all samples that tested negative for pathogenic BRAF, NRAS, HRAS and KRAS variants. Results: Seven targetable gene fusions were identified in the remaining 60 samples without known DNA variants. This includes frequently reported gene fusions such as CCDC6/RET (PTC1), PRKAR1A/RET (PTC2) and ETV6/NTRK3, and gene fusions that are less common in thyroid cancer ( TPM3/NTRK1, EML4/ALK and EML4/NTRK3 ). Of note, most gene fusions were detected in papillary thyroid carcinoma and MAPK-associated alterations in Hürthle cell carcinomas are rare (2/35). Conclusion: Targetable gene fusions were found in 12% of RAI-R thyroid carcinoma without DNA variants and can be effectively identified in formalin-fixed tissue. These gene fusions might provide a preclinical rationale to include specific kinase inhibitors in the treatment regimen for these patients. The latter intends to restore iodine transport and/or take advantage of the direct effect on tumor cell vitality once progressive disease is seen.